Potensi Senyawa Aktif Tanaman Herbal untuk Pengobatan Kanker Payudara dengan Metode Penambatan Molekuler: Review Artikel - Yunita Sari, Alma; Febrina, Ellin (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023, 2023)
Breast cancer is one of the leading causes of death in women worldwide. Breast cancer can be triggered due to physical, chemical, environmental factors and can be passed down from generation to generation through genetics. Therefore, recently, studies have been intensively conducted on the use of medicinal plants for the treatment of breast cancer as an alternative because they have minimal side effects compared to other chemotherapy. This review aims to describe medicinal plants and their active compounds that have the potential as anticancer therapy which has been carried out in silico studies with molecular anchoring methods. The method used in writing this article is a literature review both nationally and internationally over the last five years using the keywords breast cancer, molecular docking, herbal plants, anticancer, in databases such as PubMed, Cochrane, and Google Scholar. Herbal plants in in silico research that have high potential for further research as cancer therapy include 33 herbal plants with different active compounds and protein targets.